2017
DOI: 10.1002/art.40182
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCL25 and T Helper Cells Expressing CCR9 in the Salivary Glands of Patients With Primary Sjögren's Syndrome: Potential New Axis in Lymphoid Neogenesis

Abstract: Enhanced expression of CCL25 in LSGs of patients with primary SS can facilitate attraction of CCR9+ T helper cells, and these cells secrete high levels of proinflammatory cytokines when triggered with antigen or IL-7. The observed associations with B cell hyperactivity, autoimmunity, and markers of lymphoid neogenesis indicate that the CCL25/CCR9 axis plays a significant role in the immunopathology of primary SS, suggesting that this axis could represent a novel therapeutic target for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 51 publications
9
58
0
Order By: Relevance
“…In addition, there was a trend towards increased CCL20 expression ( P = .077), and a decrease of CCL27 expression ( P = .050), whereas CCL17 was not differentially expressed (Figure A). As we have previously reported, increased protein levels of CCL25 and CXCL10 in secretomes of pSS salivary gland tissue were observed . We here report that upregulated CCL25 mRNA expression significantly correlated to CXCL10 (Figure C).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…In addition, there was a trend towards increased CCL20 expression ( P = .077), and a decrease of CCL27 expression ( P = .050), whereas CCL17 was not differentially expressed (Figure A). As we have previously reported, increased protein levels of CCL25 and CXCL10 in secretomes of pSS salivary gland tissue were observed . We here report that upregulated CCL25 mRNA expression significantly correlated to CXCL10 (Figure C).…”
Section: Resultssupporting
confidence: 87%
“…Next we assessed whether mRNA and protein expression of representative chemokines that can attract CXCR3, CCR4, CCR6 and CCR10‐expressing Th cells were expressed by salivary gland tissue, either expressed as mRNA in tissue lysates or protein levels in supernatant of tissue explants . We previously reported that mRNA expression of CCL25 was significantly increased in salivary glands of pSS patients as compared to non‐SS patients . Increased CXCL10 mRNA expression as previously reported by others was confirmed (Figure A).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations